Birth Outcomes, Intervention Frequency, and the Disappearing Midwife—Potential Hazards of Central Fetal Monitoring: A Single Center Review. Issue 2 (11th February 2016) - Brown, James; McIntyre, Andrew; Gasparotto, Robyn; McGee, Therese M.
Abstract: Introduction: Many birth units use central fetal monitoring (CFM) under the assumption that greater surveillance improves perinatal outcomes. The unexpected loss of the CFM system at a tertiary unit provided a unique opportunity to evaluate outcomes and staff attitudes toward CFM. Methods: This retrospective cohort study compared patient data from 2, 855 electronically monitored women delivering over a 12‐month period, where CFM was available for the first 6 months but unavailable for the following 6 months. Primary outcomes relating to neonatal morbidity and secondary outcomes relating to intrapartum interventions were examined. Additionally, birth unit staff members were surveyed about aspects of care related to CFM. Results: There were no significant differences in perinatal outcomes between the cohorts. While unadjusted analysis suggested a lower spontaneous vaginal birth rate (55.4% vs 60.3%) and a higher cesarean delivery rate (25.1% vs 22.0%, p = 0.026), together with higher epidural (53.0% vs 49.2%, p = 0.04) and fetal blood sampling (11.8% vs 9.4%, p = 0.03) rates in the presence of CFM, these differences were lost when adjusted for prostaglandin ripening. Over half of the staff (56.0% of midwives, 54.0% of obstetricians) reported spending more time with the laboring woman in the period without CFM. Conclusions: This single institution's experience indicates that in birth units staffed for one‐to‐one care in labor, central fetal monitoring does not appear to be associated with either a benefit on perinatal outcomes or an increase in cesarean delivery and other interventions. However, it is associated with a reduction in the time a midwife spends with the laboring woman.